Separation and detection of amino acid metabolites of Escherichia coli in microbial fuel cell with CE. Issue 14 (23rd May 2016) - Wang, Wei; Ma, Lihong; Lin, Ping; Xu, Kaixuan
Abstract : In this work, CE‐LIF was employed to investigate the amino acid metabolites produced by Escherichia coli ( E. coli ) in microbial fuel cell (MFC). Two peptides, l ‐carnosine andl ‐alanyl‐glycine, together with six amino acids, cystine, alanine, lysine, methionine, tyrosine, arginine were separated and detected in advance by a CE‐LIF system coupled with a homemade spontaneous injection device. The injection device was devised to alleviate the effect of electrical discrimination for analytes during sample injection. All analytes could be completely separated within 8 min with detection limits of 20–300 nmol/L. Then this method was applied to analyze the substrate solution containing amino acid metabolites produced by E. coli .l ‐carnosine, l ‐alanyl‐glycine, and cystine were used as the carbon, nitrogen, and sulfur source for the E. coli culture in the MFC to investigate the amino acid metabolites during metabolism. Two MFCs were used to compare the activity of metabolism of the bacteria. In the sample collected at the running time 200 h of MFC, the amino acid methionine was discovered as the metabolite with the concentrations 23.3 μg/L.